The effect of exercise on the reduction of blood pressure among elderly with hypertension: a systematic literature review - Wahyuni Wahyuni; Dea Linia Romadhoni; Alinda Nur Ramadhani (International Journal of Public Health Science (IJPHS), 2022)
Elderly is a person who enters a period of achievement level of maturity that has shown deterioration, aged 60 years and older. This group which is categorized as elderly is experiencing an aging process which is marked by a decline in the body systems. Cardiovascular disease is responsible for more mortality, especially in people over 60 years of age with a history of hypertension. This study used a literature review method. A systematic search strategy was carried out by accessing the NCBI Pubmed, Elsevier, and PedRo databases online using the keywords "exercise", "hypertension" and "elderly". Based on the result of the search for articles that have been carried out, there were 90 articles. Nine articles that fit the inclusion and exclusion criteria were analyzed and all of them showed impact of exercise on reduction of blood pressure. Aerobic exercise, resistance exercise, breathing exercise and exercise in water affect the reduction of blood pressure in hypertensive elderly. Further studies are needed to determine the effectiveness of these exercises in reducing blood pressure in elderly people with hypertension.